2013
DOI: 10.1158/1535-7163.mct-13-0103-t
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Inhibitors of USP1 Target ID1 Degradation in Leukemic Cells

Abstract: Inhibitor of DNA-binding-1 (ID1) transcription factor is essential for the proliferation and progression of many cancer types including leukemia. However, the ID1 protein has not yet been therapeutically targeted in leukemia. ID1 is normally polyubiquitinated and degraded by the proteasome. Recently, it has been shown that USP1, a ubiquitin specific protease, deubiquitinates ID1 and rescues it from proteasome degradation. Inhibition of USP1 therefore offers a new avenue to target ID1 in cancer. Here, using a U… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
123
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(128 citation statements)
references
References 47 publications
5
123
0
Order By: Relevance
“…S3B). Importantly, USP1 can be therapeutically targeted by pimozide (23,27), an antipsychotic drug of the diphenylbutylpiperidine class that has limited toxicities, has been approved for use in humans, and can cross the blood-brain barrier (34). These characteristics make USP1 a possible therapeutic target in glioblastoma.…”
Section: Pdgf Signaling Regulates Usp1 Expression To Promote Survivalmentioning
confidence: 99%
See 3 more Smart Citations
“…S3B). Importantly, USP1 can be therapeutically targeted by pimozide (23,27), an antipsychotic drug of the diphenylbutylpiperidine class that has limited toxicities, has been approved for use in humans, and can cross the blood-brain barrier (34). These characteristics make USP1 a possible therapeutic target in glioblastoma.…”
Section: Pdgf Signaling Regulates Usp1 Expression To Promote Survivalmentioning
confidence: 99%
“…These findings show that PDGF signaling can upregulate Usp1 expression. Inhibition of USP1 has been previously shown to decrease proliferation of leukemia cells and spheroid formation of human glioblastoma cells (22,27). To examine whether Usp1 affects the survival of PDGF-GSCs, we infected these cells with lentiviruses encoding Usp1-targeting shRNAs (short hairpin RNAs) or a nontarget control (ShControl) and performed Annexin V/PI staining.…”
Section: Pdgf Signaling Regulates Usp1 Expression To Promote Survivalmentioning
confidence: 99%
See 2 more Smart Citations
“…11 USP1 has been identified as a key regulator in the DNA repair processes, mainly in the Fanconi anemia pathway and Translesion DNA synthesis by regulating ubiquitination status of FANCD2 and PCNA, 12,13 Mono-ubiquitinated FANCD2 and PCNA serve as a platform to recruit DNA repair proteins to DNA damage sites, [14][15][16] and USP-induced deubiquitination of FANCD2 and PCNA is crucial for the correct function of DNA repair pathway. 17,18 Indeed, Usp1 gene deletion in mice 18 and USP1 inhibition by small molecules displayed chemosensitizing effects against DNA damaging agents, [19][20][21] indicating that USP1 is required for an efficient DNA repair activity. Besides DNA repair-related function, recent study reveals that increased level of USP1 is found in human osteosarcoma cell lines.…”
Section: Introductionmentioning
confidence: 99%